Preparation of LiBOB via rheological phase method and its application to mitigate voltage fade of Li1.16[Mn0.75Ni0.25]0.84O2 cathode. Issue 105 (13th October 2015) - Lian, Fang; Li, Yang; He, Yi; Guan, Hongyan; Yan, Kun; Qiu, Weihua; Chou, Kuo-Chih; Axmann, Peter; Wohlfahrt-Mehrens, Margret
Abstract : High-purity LiBOB, synthesized via novel rheological phase reaction method without further recrystallization, mitigated voltage-fade of Li-rich cathode as electrolyte additive. Abstract : Lithium bis(oxalato)borate (LiBOB) was synthesized via a novel rheological phase reaction method without any recrystallization procedure. The purity of the as-obtained LiBOB has been identified in comparison with the commercial sample and our sample prepared from solid-state reaction method. The results of XRD, ICP, and 11 B NMR demonstrate that high pure LiBOB has been synthesized via rheological phase reaction method with significantly simplified synthetic process. Moreover, LiBOB sample has been investigated as electrolyte additive to improve the electrochemical performances of high-energy lithium-rich layered oxide. The cycling performances imply that 0.03 M and 0.05 M LiBOB additive can mitigate discharge voltage fade and enhance the cycle stability of Li1.16 [Mn0.75 Ni0.25 ]0.84 O2 material. The CV, EIS and XPS data indicate that LiBOB oxidizes at ∼4.3 V ( vs. Li/Li + ) on the cathode surface during the first charge to form a specific SEI layer with larger amount of organic species and fairly less content of LiF, which decreases the interfacial polarization and protects the active material from surface degradation, thereby mitigates the voltage-fade of Li-rich cathode.